The Effect of Labor Position during Second Stage of Labor on Mode of Delivery in Low Risk Women - Arikatla, Sai Aiswarya; Dabral, Anjali; Bharti, Rekha; Kumari, Suman; Sarin, Madhavi; Goyari, Poojapreeti (Universitas Andalas, 2025)
Background: Delivery in an upright position aligns the uterine forces with the pelvic cavity and decreases the duration of the second stage of labor. The upright position is also reported to reduce the risk of cesarean deliveries. The present study was planned to compare the mode of delivery in women delivering in supine versus upright (squatting and kneeling) positions. Material and Methods: This prospective observational study was conducted in a tertiary care center's Obstetrics and Gynecology department. Women in early stage of labor were counseled about various labor positions. Women who adopted supine, kneeling, and squatting positions in second stage of labor were divided into three groups according to their choice. The women were followed for effect of position in second labor stage on delivery mode. Results: A total of 210 women were enrolled in the study. The three groups were comparable in terms of demographic parameters, except that women in the supine group were younger than women assuming upright positions in the second stage of labor. The rate of cesarean section and moderate/severe PPH was increased in women assuming the supine position in the second stage of labor. However, the difference was not statistically significant, p=0.209 and 0.223, respectively. The mean duration of the second stage of labor was significantly increased in women delivering in the supine position, p=0.001. Conclusion: Upright (kneeling and squatting) position significantly decreases duration of second stage of labor but is not associated with a difference in cesarean delivery rate compared to women in the supine group.